Nitrous oxide emissions from the surface of the Three Gorges Reservoir - Zhu, Dan; Chen, Huai; Yuan, Xingzhong; Wu, Ning; Gao, Yongheng; Wu, Yan; Zhang, Yongmei; Peng, Changhui; Zhu, Qiu’an; Yang, Gang; Wu, Jianghua (Ecological Engineering, 2013)

Carbon accumulation and sequestration of lakes in China during the Holocene - Wang, Mei; Chen, Huai; Yu, Zicheng; Wu, Jianghua; Zhu, Qiu'an; Peng, Changhui; Wang, Yanfen; Qin, Boqiang (Global Change Biology, 2015)
Abstract Understanding the responses of lake systems to past climate change and human activity is critical for assessing and predicting the fate of lake carbon (C) in the future. In this study, we synthesized records of the sediment accumulation from 82 lakes and of C sequestration from 58 lakes with direct organic C measurements throughout China. We also identified the controlling factors of the long‐term sediment and C accumulation dynamics in these lakes during the past 12 ka (1 ka = 1000 cal yr BP ). Our results indicated an overall increasing trend of sediment and C accumulation since 12 ka, with an accumulation peak in the last couple of millennia for lakes in China, corresponding to terrestrial organic matter input due to land‐use change. The Holocene lake sediment accumulation rate ( SAR ) and C accumulation rate ( CAR ) averaged (mean ± SE ) 0.47 ± 0.05 mm yr −1 and 7.7 ± 1.4 g C m −2 yr −1 in China, respectively, comparable to the previous estimates for boreal and temperate regions. The SAR for lakes in the East Plain of subtropical China (1.05 ± 0.28 mm yr −1 ) was higher than those in other regions ( P < 0.05). However, CAR did not vary significantly among regions. Overall, the variability and history of climate and anthropogenic interference regulated the temporal and spatial dynamics of sediment and C sequestration for lakes in China. We estimated the total amount of C burial in lakes of China as 8.0 ± 1.0 Pg C. This first estimation of total C storage and dynamics in lakes of China confirms the importance of lakes in land C budget in monsoon‐influenced regions.

Carbon dynamics of peatlands in China during the Holocene - Wang, Mei; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Yang, Gang; Wu, Jianghua; He, Yixin; Gao, Yongheng; Tian, Jianqing; Zhao, Xinquan (Quaternary Science Reviews, 2014)

Higher recent peat C accumulation than that during the Holocene on the Zoige Plateau - Wang, Mei; Yang, Gang; Gao, Yongheng; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Wu, Jianghua; He, Yixin; Tian, Jianqing; Zhao, Xinquan; et al. (Quaternary Science Reviews, 2015)

The carbon stock of alpine peatlands on the Qinghai–Tibetan Plateau during the Holocene and their future fate - Chen, Huai; Yang, Gang; Peng, Changhui; Zhang, Yao; Zhu, Dan; Zhu, Qiuan; Hu, Ji; Wang, Mei; Zhan, Wei; Zhu, Erxiong; Bai, Zengzhi; Li, Wei; et al. (Quaternary Science Reviews, 2014)

The impacts of climate change and human activities on biogeochemical cycles on the Q inghai‐ T ibetan P lateau - Chen, Huai; Zhu, Qiuan; Peng, Changhui; Wu, Ning; Wang, Yanfen; Fang, Xiuqing; Gao, Yongheng; Zhu, Dan; Yang, Gang; Tian, Jianqing; Kang, Xiaoming; Piao, Shilong; et al. (Global Change Biology, 2013)
Abstract With a pace of about twice the observed rate of global warming, the temperature on the Qinghai‐Tibetan Plateau (Earth's ‘third pole’) has increased by 0.2 °C per decade over the past 50 years, which results in significant permafrost thawing and glacier retreat. Our review suggested that warming enhanced net primary production and soil respiration, decreased methane ( CH 4 ) emissions from wetlands and increased CH 4 consumption of meadows, but might increase CH 4 emissions from lakes. Warming‐induced permafrost thawing and glaciers melting would also result in substantial emission of old carbon dioxide ( CO 2 ) and CH 4 . Nitrous oxide ( N 2 O ) emission was not stimulated by warming itself, but might be slightly enhanced by wetting. However, there are many uncertainties in such biogeochemical cycles under climate change. Human activities (e.g. grazing, land cover changes) further modified the biogeochemical cycles and amplified such uncertainties on the plateau. If the projected warming and wetting continues, the future biogeochemical cycles will be more complicated. So facing research in this field is an ongoing challenge of integrating field observations with process‐based ecosystem models to predict the impacts of future climate change and human activities at various temporal and spatial scales. To reduce the uncertainties and to improve the precision of the predictions of the impacts of climate change and human activities on biogeochemical cycles, efforts should focus on conducting more field observation studies, integrating data within improved models, and developing new knowledge about coupling among carbon, nitrogen, and phosphorus biogeochemical cycles as well as about the role of microbes in these cycles.